Possible ways for post‐treatment of biologically treated wastewater from yeast factory - Blonskaja, Viktoria; Zub, Sergei (Journal of Environmental Engineering and Landscape Management, 2009)
The effluents, which are formed from the waste in the process of production of yeast and molasses, contain a large amount of colouring substances (melanoidins, etc.) and can give dark brown painting to the effluent leading to high organic load on the wastewater treatment plant. The purpose of this study was estimation of the process of coagulation as possible method for the post‐treatment of effluents of yeast industry. The experiments on the coagulation were carried out using biologically purified effluents of Salutaguse yeast factory. This effluent had relatively high residual content of COD (with the effectiveness of treatment — 90%) and brown colour. Different coagulants and flocculants were studied under laboratory conditions. The most effective coagulants FeCl3˙6H2O and Al2 (SO4) 3 were studied additionally. The results of this experiment showed a significant decrease of colour and also concentration of COD. Economic analysis for the possible application of coagulants and ozone for the post‐treated effluents of yeast factory was also made. The obtained data showed that coagulants and ozone could be used in the process of the post‐treatment of effluents of yeast industry for the purpose of decreasing the colour and general concentration of pollutants, however, these processes are very expensive. Galimi papildomi mielių gamyklos biologiškai valytų nuotekų valymo būdai Santrauka. Nuotekų, susidarančių pramoniniuose procesuose naudojant mieles bei melasą, sudėtyje esti dideli kiekiai dažančių medžiagų (melanoidų). Jie nuotekas nudažo tamsiai rudai, o valymo įrenginiams tenka didelės organinių medžiagų apkrovos. Tyrimo tikslas buvo įvertinti koaguliacijos procesą kaip galimą papildomą mielių pramonės nuotekų valymo metodą. Koaguliacijos eksperimentams buvo naudojamos biologiškai valytos Salutaguso mielių gamyklos nuotekos. Nustatyta didelė šių nuotekų liekamoji organinių medžiagų vertė (valymo efektyvumui esant 90 %), nuotekos buvo rudos. Laboratorinėmis sąlygomis ištirta įvairūs koaguliantai ir flokuliantai. Efektyviausieji koaguliantai – FeCl3 · 6H2O ir Al2 (SO4 )3 buvo išanalizuoti papildomai. Eksperimento rezultatai – žymiai pašviesėjo nuotekų spalva, sumažėjo organinių medžiagų koncentracija. Atlikta ekonominė analizė, įvertinta koaguliantų ir ozono taikymas biologiškai išvalytoms mielių gamyklos nuotekoms valyti papildomai, kad pašviesėtų nuotekų spalva, ir suminė organinių medžiagų koncentracija būtų mažesnė. Šie procesai yra itin brangūs. Reikšminiai žodžiai: koaguliacija, spalva, ozonavimas, papildomas valymas, mielių pramonės nuotekos. Возможные пути доочистки биологически очищенных сточных вод дрожжевого завода Резюме. Сточные воды, образующиеся от использования в процессе производства дрожжей мелассы, содержат большое количество красящих веществ (меланоидинов), которые придают сточной воде темно-коричневую окраску и приводят к высокой органической нагрузке на очистные сооружения. Целью исследования была оценка процесса коагулирования как возможного метода доочистки сточных вод дрожжевой промышленности. В экспериментах по коагулированию была использована биологически очищенная сточная вода Салутагуского завода по производству дрожжей. Сток имел относительно высокое остаточное содержание органических веществ (при эффективной очистке в 90%) и коричневый цвет. Различные коагулянты и флокулянты были изучены в лабораторных условиях. Наиболее эффективные коагулянты FeCl3 ·6H2O и Al2 (SO4 )3 были изучены дополнительно. В результате эксперимента удалось добиться значительного уменьшения интенсивности цвета и концентрации органических веществ. Был произведен экономический анализ с целью возможного применения коагулянтов и озона для процесса доочистки биологически очищенных стоков завода по производству дрожжей. Коагулянты и озон можно использовать в процессе доочистки стоков биологически очищенных вод дрожжевой промышленности для уменьшения цветности и общей концентрации органических веществ. Эти процессы, однако, очень дороги. Ключевые слова: коагуляция, цвет, озонирование, дополнительная очистка, сточные воды дрожжевой промышленности. First Published Online: 14 Oct 2010